Exposição materna ao ditelureto de difenila causa alterações comportamentais e bioquímicas em filhotes de rato - Stangherlin, Eluza Curte (2007)
The brain of rodents presents a rapid development after birth. Thus, the functioning of the nervous system can be modified by action of xenobiotics during this period. The alterations can be evaluated by the performance of animals in several behavioral tests, which are the end point of neural functions or still by analysis of biochemical parameters. Diphenyl ditelluride, an organottelurium compound, was the xenobiotic target of this study. The objective of the present was to evaluate the effects of maternal exposure to diphenyl ditelluride, during the suckling period, in behavioral and biochemical parameters in rat pups. The results obtained revealed disinhibitory tendencies, evidenced by performance of animals in the elevated plus-maze. Data of this study also showed that animals exposed to diphenyl ditelluride presented cognitive impairment, observed in the object recognition memory task. Therefore, we assume that diphenyl ditelluride can pass for pups through maternal milk, probably in view of its liposolubility. The investigation of the possible mechanisms of action by which diphenyl ditelluride induced behavioral changes revealed that this compound inhibited glutamate uptake and did not alter glutamate release in sinaptossomas of total brain. These events could promote an increase of glutamate in the synaptic cleft. However, the aiding of the glutamatergic neurotransmission seems to be more related to inhibitory events or still, of facilitation of the processes related with the cognition/memory, that are, contrary behaviors to the observed ones in this study. Thus, the alteration of the homeostasis of the glutamatergic system caused by diphenyl ditelluride seems not to be directly related to the observed behavioral alterations. An inhibition in the activity of cerebral Na+,K+-ATPase was observed. Some studies have reported the inhibition of Na+,K+-ATPase activity with the impairment of memory. Thus, this is one of the probable mechanisms related to the cognitive impairment of animals. Moreover, the biochemistry evaluation revealed that the exposure to diphenyl ditelluride caused a series of alterations in the cerebral oxidative status of the pups. The most affected cerebral structures by oxidative stress were hippocampus and the striatum. In these regions, it was observed an increase in lipid peroxidation and an inhibition of enzymes superoxide dismutase, catalase and d-aminolevulinate dehydratase activities. Probably the inhibition of the activity of these enzymes was a consequence of oxidative stress. Striatum had an increase of the levels of ascorbic acid and non-protein thiols. An increase of the levels of non-protein thiols was found only in the cortex. The increase of the levels of these two non-enzymatic antioxidants can have been an adaptive response of cerebral tissues to oxidative stress. The oxidative stress found in specific cerebral regions probably is involved in the mechanisms by which diphenyl ditelluride caused behavioral alterations. In fact, hippocampus and striatum, the most affected cerebral regions related to disinhibition and cognition.